Music Selection and Use Strategies in Music Therapy - Wang, Kun; Zhang, Ke (International Journal of Global Economics and Management, 2024)
Music therapy, as a kind of non-pharmacological treatment, is gradually gaining attention in China. The aim of this thesis is to discuss the issues related to music selection and use of strategies in music therapy. Firstly, the definition and basic principles of music therapy as well as the physiological and psychological effects of music on human beings are introduced. Secondly, the principles and criteria of music selection are analysed, including the characteristics of music genres, individual differences of patients and the evaluation of music therapy effects. Then, specific methods of music application strategies, such as playing, listening and composing, as well as the combination of music with other therapeutic means, are explored. Then, through case studies, the application of music selection and use strategies in actual therapy is further elaborated. In addition, corresponding countermeasures are proposed to address the challenges faced in music therapy.